Analisis Framing Personal Branding Agus Harimurti Yudhoyono pada Detik.Com - Wegga Miftakhul Juliani; Nur Maghfirah Aesthetika (Kanal: Jurnal Ilmu Komunikasi, 2018)
This research aims to describe Agus Harimurti Yudhoyono personal branding by Detik.com. This research used qualitative approach. Framing analysis did by using of Pan and Kosicki analysis model. There are 4 structure analysis in the Pan and Kosicki framing analysis, such as thematic, scripts, semantic and rhetorical. The results showed that framing the news that conducted by Detik.com to Agus Harimurti Yudhoyono was well done. Agus Harimurti Yudhoyono imaged as a figure who was very caring with progress, prosperity and peacefull in Jakarta.